STUDI KASUS TENTANG AKIBAT DARI PROKRASTINASI YANG DILAKUKAN OLEH KONSELI DI SMA NEGERI 5 BUKITTINGGI - Syakila Errina Fitri; Dodi Pasilaputra (JIP: Jurnal Ilmu Pendidikan, 2024)
This research is entitled a case study about students who feel lazy in studying, which makes the counselee not have the motivation to study and often delays going to school. Counselees who often delay going to school, causing the counselee to come to school late, are caused by the counselee often feeling lazy about going to school. Generally, the problem in this research is how to help counselees who feel lazy about studying in class XI.F4 at SMA N 5 Bukittinggi. While the aim is to obtain an objective picture of the characteristics, causal factors, and appropriate alternative assistance to be used to overcome this problem. The problem of counselees who find it difficult to carry out academic procrastination behavior in class XI. F4 SMA Negeri 5 Bukittinggi with MAR counselors. The approach used in this research is qualitative using descriptive methods and the form of research is a case study. In this research, individual counseling was carried out to help solve the client's problems by changing the client's thinking pattern from an irrational one to a rational one using the behavioral counseling approach model.